The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/480728
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Anesthesia versus Normotensive Anesthesia during Major Maxillofacial Surgery: A Review of the Literature

Abstract: Steady blood pressure within normal limits during surgery is one of the markers of the ideal and skillful anesthesia. Yet, reduced blood pressure is advantageous in some settings because it can contribute to a reduction in overall blood loss and improve the surgical field conditions. Controlled hypotension during anesthesia or hypotensive anesthesia is often used in major maxillofacial operations. Since hypotensive anesthesia carries the risk of hypoperfusion to important organs and tissues, mainly the brain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 59 publications
0
31
0
4
Order By: Relevance
“…with a MAP of 50-65 mm Hg during major maxillofacial surgeries. [ 24 ] Hypotensive anesthesia induced by using sodium nitroprusside or nitroglycerine in mandibular osteotomy to achieve MAP 60-70 mm Hg was found to be absolutely safe and associated with no significant increase in pyruvate, lactate, or glucose levels. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…with a MAP of 50-65 mm Hg during major maxillofacial surgeries. [ 24 ] Hypotensive anesthesia induced by using sodium nitroprusside or nitroglycerine in mandibular osteotomy to achieve MAP 60-70 mm Hg was found to be absolutely safe and associated with no significant increase in pyruvate, lactate, or glucose levels. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…No intraoperative blood salvage device was arranged because, although it has been demonstrated that a high percentage of patients presenting for cancer surgery actually have already circulating tumor cells, is a question yet left unanswered if adding tumor cells into the circulation could worsen prognosis [17] , [18] . During surgery, one of the best and safest way to prevent excessive bleeding, is hypotensive anesthesia (MAP to 50–65 mmHg) using propofol and remifentanil, to reduce the extent of intraoperative blood loss [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Hypotensive anesthesia is defined as reduction of systolic blood pressure to 80-90 mmHg or reduction of mean arterial pressure (MAP) by 30% from the base line [10]. As blood perfusion to the surgical site is reduced, the amount of bleeding is also reduced producing improved surgical field, less total blood loss and possibly shorter operating time [10,11]. For hypotensive anesthesia to be produced safely, only patients with good compensatory mechanisms are selected.…”
Section: Hypotensive Anesthesiamentioning
confidence: 99%